Proper actions of lamplighter groups associated with free groups - De Cornulier, Yves; Stalder, Yves; Valette, Alain (My University, 2008)
Given a finite group H and a free group F-n, we prove that the wreath product H (sic) F-n admits a metrically proper, isometric action on a Hilbert space.